2016
DOI: 10.1177/2047487316657671
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in case fatality following an acute ischaemic heart disease event in New Zealand: ANZACS-QI 13

Abstract: Major ethnic inequalities in IHD case fatality occur with and without associated hospitalisations. Improvements in both primary prevention and hospital care will be required to reduce inequalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…When adjusted for age, sex and NT-proBNP levels, Māori ethnicity was associated with higher risk of adverse outcomes compared with European ethnicity, consistent with known health inequities 2 3. However, when including the clinical summary score, the association between Māori ethnicity and risk of death or CV readmission was attenuated and not statistically significant, indicating that the prior increased risk for Māori participants was at least partly explained by the 20 clinical factors in the score.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…When adjusted for age, sex and NT-proBNP levels, Māori ethnicity was associated with higher risk of adverse outcomes compared with European ethnicity, consistent with known health inequities 2 3. However, when including the clinical summary score, the association between Māori ethnicity and risk of death or CV readmission was attenuated and not statistically significant, indicating that the prior increased risk for Māori participants was at least partly explained by the 20 clinical factors in the score.…”
Section: Discussionmentioning
confidence: 69%
“…In New Zealand (NZ), there are persistent inequitable outcomes by ethnicity, with worse outcomes for Māori (the Indigenous people of NZ) and Pacific people. The causes of these inequities are multifactorial, and they remain after accounting for known modifiable clinical risk factors 2 3…”
Section: Introductionmentioning
confidence: 99%
“…It is of concern that Māori and Pacific peoples are overrepresented in patients with CKD in New Zealand In this study, only 20% of those with normal renal function were Maori or Pacific but over half of those with stage 5 CKD identified as Māori or Pacific. Previous analysis of the ANZACS‐QI investigators has shown a 50% increased risk of death in patients of Māori and Pacific ethnicity compared with those of European descent . This is despite Māori and Pacific peoples being, on average, younger at the time of ACS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Māori and Pacific people are significantly more likely than Europeans to die from CHD before reaching hospital (Grey et al, 2016a), are less likely to call an ambulance when experiencing an acute coronary syndrome (ACS) (Garofalo et al, 2012), and are more likely to experience delays to defibrillation (Kerr et al, 2019). Such delays to care are crucially important; definitive medical treatment for ACS should be started as soon as possible to prevent life-threatening complications, and ideally within 1 hour of symptom onset (Chew et al, 2016; Moser et al, 2006; Norris, 2005).…”
Section: Introductionmentioning
confidence: 99%